2019
DOI: 10.1155/2019/4038319
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Pediatric Traumatic Brain Injury at Sylvanus Olympio University Hospital of Lomé in Togo

Abstract: Introduction. Severe pediatric traumatic brain injury (pTBI) is a leading cause of disability and death in children worldwide. Children victims of pTBI are admitted to the Sylvanus Olympio University Hospital (SOUH) at the multipurpose Intensive Care Unit (ICU). We aimed in this study to describe the epidemiologic characteristics and outcomes of pTBI patients admitted in this ICU. Patients and Methods. This study was conducted at the ICU of SOUH of Lome. It was a retrospective study based on patients’ records … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…[ 7 10 ] TBI resulting from closed head injury (CHI) is one of the main causes of disability and death in children. [ 11 , 12 ] According to the Glasgow Coma Scale (GCS), TBI is usually divided into mild (GCS = 13–15), moderate (GCS = 9–12), and severe (GCS = 3–8). Children with mild TBI account for more than 80% of all injuries.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 10 ] TBI resulting from closed head injury (CHI) is one of the main causes of disability and death in children. [ 11 , 12 ] According to the Glasgow Coma Scale (GCS), TBI is usually divided into mild (GCS = 13–15), moderate (GCS = 9–12), and severe (GCS = 3–8). Children with mild TBI account for more than 80% of all injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Thirty (30) complete articles were evaluated for eligibility and 13 papers (n = 40685) [ 4 , 17 , 12 , 23 – 32 ] met the inclusion criteria and were included in the final qualitative and meta-analysis. However, 4 studies [ 26 , 29 31 ] were included in the meta-analysis for the pooled incidence ( Fig 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This is not surprising as the study using US trauma registry used only severe children with TBI cases and hence expected that mortality should be high. In fact, studies have identified a strong correlation between severe TBI and in-hospital mortality [ 30 , 31 , 38 ]. The high case fatality in SSA could be ascribed to a variety of factors, including the high severity cases measured by GCS [i.e., 7.7% -40.2%] seen in the current review, infrastructural gap in pre-hospital and in-patients’ management that exist in the sub-region as well as the limited specialized Intensive Care Unit for neuro-surgical cases to manage high severe pediatric with TBI in SSA.…”
Section: Discussionmentioning
confidence: 99%
“…Among adults over 60 with TBI, cerebral contusions are found in around 18% of cases ( 5 ). In pediatric TBI, brain contusion (55.9%) is also frequently observed ( 6 ). These contusions not only cause loss of function but also pose a significant threat to healthy brain tissue due to the toxic nature of blood.…”
Section: Introductionmentioning
confidence: 99%